2018
DOI: 10.1111/lam.12831
|View full text |Cite
|
Sign up to set email alerts
|

Solar irradiance limits the long-term survival ofListeria monocytogenesin seawater

Abstract: Listeria monocytogenes is a food-borne bacterial pathogen capable of causing the life-threatening infection, listeriosis. In seafood the route of contamination from the environment is often not well understood as this pathogen is not generally thought to survive well in seawater. Here we provide evidence that L. monocytogenes is capable of surviving for long periods of time in seawater when light is excluded. Sunlight is demonstrated to have a significant effect on the survival of this pathogen in seawater, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The different responses observed in the present study and in the study by O'Donoghue et al (10) are likely due to differences in doses and wavelengths of the light the bacteria are exposed to. Similar to the results from the present study, NicAogáin et al did not observe any significant difference in survival between the blue light receptor mutant (the strain used in the present study) and the wild-type EGDe background strain, when exposed to blue light (470 nm) in seawater (42). However, these researchers found that exposure to blue light reduced the survival of the ΔsigB mutant and suggested that the activity of SigB was regulated by other pathways than via the blue light receptor (42).…”
Section: Light-induced Expression Of Two Diguanylate Cyclases Responsible For the Synthesis Of C-di-gmpsupporting
confidence: 91%
“…The different responses observed in the present study and in the study by O'Donoghue et al (10) are likely due to differences in doses and wavelengths of the light the bacteria are exposed to. Similar to the results from the present study, NicAogáin et al did not observe any significant difference in survival between the blue light receptor mutant (the strain used in the present study) and the wild-type EGDe background strain, when exposed to blue light (470 nm) in seawater (42). However, these researchers found that exposure to blue light reduced the survival of the ΔsigB mutant and suggested that the activity of SigB was regulated by other pathways than via the blue light receptor (42).…”
Section: Light-induced Expression Of Two Diguanylate Cyclases Responsible For the Synthesis Of C-di-gmpsupporting
confidence: 91%